SOCIOCULTURAL FUNCTIONS OF AESTHETIC CULTURE UNDER THE TRANSFORMATIONAL CONDITIONS OF THE MODERN UKRAINIAN SICIETY - Мокляк, Л. І. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
Sociocultural functions of aesthetic culture, its place and role under the transformational conditions of the modern Ukrainian society are analyzed.